Using the dynamic, expanding liquid-liquid interface in a Hele-Shaw cell in crystal growth and nanoparticle assembly - Rautaray, D; Kavathekar, R; Sastry, M (Faraday Discussions, 2005)
The liquid-liquid interface has been used with considerable success in the synthesis of advanced materials ranging from (bio)minerals to inorganic membranes to nanoparticles. In almost all such cases, the interface is static. The Hele-Shaw cell in which a viscous fluid is displaced by a less viscous one in a constrained manner has been invaluable in the study of dynamic instabilities at interfaces and in the study of viscous fingering pattern formation. However, the potential of the Hele-Shaw cell in carrying out reactions at the interface between the two fluids leading to the formation of inorganic materials has been largely unrecognized and underexploited. Realizing that the dynamic liquid-liquid interface in a Hele-Shaw cell would provide opportunities to control a variety of time-scales associated with material formation, we have started a program on the use of the Hele-Shaw cell in materials synthesis. In this discussion paper, we present some of our recent results on the growth of calcium carbonate crystals in the Hele-Shaw cell by the reaction of Ca2+ ions electrostatically complexed with carboxylate ions pinned to the interface with carbonate ions present in the aqueous part of the biphasic reaction medium. We show that both polymorph selectivity and the morphology of the crystals may be modulated by varying the experimental conditions in the cell. We also discuss the possibility of using the dynamic interface in the Hele-Shaw cell to cross-link gold nanoparticles in water through bifunctional linkers present in the oil phase and investigate the nature of the structures formed.